Estudo teórico de nanocones e monocamadas dopadas com gálio - Alves Júnior, Elias Brito (2017)
The recent advances in technology, in particular the nanotechnology, lead to the new investigations in the cientiﬁc enviroment and contribute toe new ways to investigate the nature. In the present work, we show some investigations that are consequences of theses advances. First of all, we investigate the behavior between two nanocones that have interactions. Initially we study the carbon nanocones, that derived from fullerene and used as nanotube caps, but with many applications when sinthetize individually. The chapter about carbon nanocones is composed by investigation of the energetic stability between two nanocones with same disclination angle and a composition of two nanocones with different disclination swith the goal to ﬁnd the ideal distance between this cones overlapping. Beyond that, we rotated the upper cone with speciﬁc angles, that generate the Moire pattern to investigate the inﬂuence of rotation over the electronic states. It was identiﬁed that the rotated conﬁgurations rather most stable than not rotated. This occurs because this cones are similar to the Bernal stacked graphite. In the chapter about the hybrid nanocones, we calculated the sames properties from carbon nanocones, however, with the speciﬁc features of the nancones that involve the boron,nitrogenand carbon atoms, what gives the insulating character to the cones. All conﬁgurations showed different atoms on the defect line and this factor is responsible to change the formation energy, interaction energy and the electronic states, mainly on the gap region. The double-walled nanocones with only nitrogen or boron atoms on the defect line as most stable when we rotated the upper cone. This is due the greater distance between the atoms located on the defect line. To the Otherwise, the conﬁgurations with carbon and the composition between boron and nitrogen has most stability without rotation, and this garantee more interaction between these atoms. The following chapter approaches the effects of dopping with gallium atoms in graphene monolayers. We use different concentrations and the stability showed a different behavior when odd numbers or even numbers of gallium atoms was putted in the structure. The presence of different numbers of gallium atoms in each sub-lattice of graphene deforms the different way the supercell. This affect directly the electronic properties. The odd numbers of gallium atoms keeps the metallic character, with states crossing the Fermi Level, while the even numbers to dopping open the gap, leading to the semiconductor behavior. To the calculated optical properties, the dopping with gallium atoms reduces the optical absorption and conductivity on the infrared and ultraviolet region, what garantee the control with a few atoms. Finally, we dopped a monolayer ofh-BN with gallium atoms. Through the simulated annealing algorithm, each process with different gallium atoms, monotomic bonds like B-B and N-N arises and this bonds affects directly the properties. The distortions suffered with the dopping affects mainly the substitution the nitrogen and the B-N pair to the gallium atoms, that leads the dissociation of the monolayer. When we substitute the gallium to the boron, we growing linearly the numbers of the Ga. The electronic properties was affected with reduction of the gap due the states that arise on this region due the monotomic bonds. For the optical properties, states on the visible region arises, what shows the inﬂuence of this bonds due the simulated annealing algorithm.